Xylohypha bantiana multiple brain abscesses in a patient with systemic lupus erythematosus - AlHabib, Khalid F (Pulsus Group Inc, 2003)
Xylohypha bantiana is a rare cause of cerebral fungal infection (phaeohyphomycosis). We report on a 72-year-old man who, while taking several immunosuppressive medications for systemic lupus erythematosus, presented with multiple bilateral cerebral abscesses caused by X bantiana. The lesions were not surgically amenable and the patient died two months after discontinuing antifungal therapy.